Eligibility and Predictors for Acute Revascularization Procedures in a Stroke Center. Issue 7 (July 2016) - Vanacker, Peter; Lambrou, Dimitris; Eskandari, Ashraf; Mosimann, Pascal J.; Maghraoui, Ali; Michel, Patrik
Abstract : Background and Purpose—: Endovascular treatment (EVT) is a new standard of care for selected, large vessel occlusive strokes. We aimed to determine frequency of potentially eligible patients for intravenous thrombolysis (IVT) and EVT in comprehensive stroke centers. In addition, predictors of EVT eligibility were derived. Methods—: Patients from a stroke center–based registry (2003–2014), admitted within 24 hours of last proof of usual health, were selected if they had all data to determine IVT and EVT eligibility according to American Heart Association/American Stroke Association (AHA/ASA) guidelines (class I–IIa recommendations). Moreover, less restrictive criteria adapted from randomized controlled trials and clinical practice were tested. Maximum onset-to-door time windows for IVT eligibility were 3.5 hours (allowing door-to-needle delay of ⩽60 minutes) and 4.5 hours for EVT eligibility (door-to-groin delay ⩽90 minutes). Demographic and clinical information were used in logistic regression analysis to derive variables associated with EVT eligibility. Results—: A total of 2704 patients with acute ischemic stroke were included, of which 26.8% were transfers. Of all patients with stroke arriving at our comprehensive stroke center, a total proportion of 12.4% patients was eligible for IVT. Frequency of EVT eligibility differed between AHA/ASA guidelines and less restrictive approach: 2.9% versus 4.9%, respectively, of all patients with acute ischemic stroke and 10.5% versus 17.7%, respectively, of all patients arriving within <6 hours. Predictors for AHA–EVT eligibility were younger, shorter onset-to-admission delays, higher National Institutes of Health Stroke Scale (NIHSS), decreased vigilance, hemineglect, absent cerebellar signs, atrial fibrillation, smoking, and decreasing glucose levels (area under the curve=0.86). Conclusions—: Of patients arriving within 6 hours at a comprehensive stroke center, 10.5% are EVT eligible according to AHA/ASA criteria, 17.7% according to criteria resembling randomized controlled trials, and twice as many patients are IVT eligible (36.2%). Abstract : Supplemental Digital Content is available in the text.